Evaluation of hepatoprotective effect of ethanolic extract of eugenia jamolana (njaval) leaves on paracetamol induced toxicity in rats - Midhun M V (Department of Pharmacology and Toxicology, College of Veterinary and Animal Sciences, 2008)
The present study is undertaken to evaluate the hepatoprotective effect of Eugenia jambolana (Njaval) leaves on paracetamol induced toxicity in rats.